Community Empowerment Based on Ecotourism in Sukalaksana Village, Samarang District, Garut Regency, West Java Province - Nadya Kurnia Sansita (International Journal Labs, 2025)
Community empowerment is an important approach in village development, especially in the context of ecotourism-based tourism village development. This study aims to analyze the process of community empowerment in Sukalaksana Village, Garut Regency, with an emphasis on changes in awareness, capacity building, and changes in community structure and social relations. This study uses a qualitative approach with a case study method. Data collection was carried out through in-depth interviews with the Village Head, the Chairman of Village-Owned Enterprises (BUMDes), the Head of the Garut Regency Tourism and Culture Office, the Head of the Treasury Division of BPKAD Garut Regency, community leaders, and residents who are directly involved in the management of the tourist village, and supported by participatory observation and documentation studies. Data analysis was carried out thematically by linking field findings to the framework of Hogan's empowerment theory. The results of the study show that the community empowerment process in Sukalaksana Village is carried out by local actors who start from scratch so as to produce a change in the mindset of the community. This change in mindset encourages increased community participation in village decision-making and activities, as well as strengthening social and economic capacity through the use of local potential based on ecotourism. In addition, the formation and strengthening of the role of BUMDes contributes to social, economic and environmental changes, characterized by the involvement of various community groups, including women, in the management of village resources. This study concludes that ecotourism-based community empowerment is a sustainable process that not only impacts economic improvement, but also produces interrelated social and environmental changes. These findings affirm the importance of an empowerment approach based on local potential and community participation as a sustainable village development strategy.